Paediatric acute kidney injury management in an African setting - Mc, Culloch Mignon (Department of Paediatrics and Child Health, 2025)
Kidney disease is a growing public health concern, affecting adults but also children who face challenges of access in low-resource settings including Africa. We studied our own paediatric dialysis results, our fellows training in the field of acute kidney injury (AKI) and reviewed innovative techniques for acute peritoneal dialysis, which also included costing of forms of acute dialysis in children. Dialysis for Paediatric AKI in Cape Town, South Africa A review of our dialysis database of over 593 cases for AKI at Red Cross War Memorial Children's Hospital (RCWMCH) over 20 years focusing on ‘Peritoneal dialysis (PD) first for our paediatric AKI program' whereby most children received PD as a first modality, despite having extracorporeal dialysis available. Types of dialysis were reviewed, as well as complications with acceptable outcomes described. Lessons learned from regional training of paediatric nephrology fellows in Africa There is a significant shortage of staff managing children with AKI in Africa and this is a review of our training program (1999 – 2021) of 38 African paediatric nephrology fellows. The emphasis is on training in paediatric AKI, including a review of hands-on training and length of training time in our unit, including subspecialty exams and research. Although a 100% return rate was noted to their home institutions, a survey was performed of our trainees on return home. This survey identified specific challenges faced and allowed for appropriateness of our training. Use of locally prepared peritoneal dialysis fluid for acute PD in children and infants in Africa including documentation of innovation of PD catheters and fluid, in the absence of conventional equipment, with good outcomes in our centre (4% peritonitis rate). Costing of our dialysis modalities included a short review in costing of dialysis modalities for acute kidney injury in our program. Conclusion: My thesis presents the development of services for children with acute kidney injury in Africa over 20 years. For me the future should be that ‘No child should die of acute kidney injury, without an attempt at peritoneal dialysis'.